RAISING AWARENESS OF HEART ATTACKS ON LANSIA IN THE WONOKROMO VILLAGE AREA - Yurike Septianingrum; Siti Damawiyah (Community Service Journal of Indonesia, 2021)
Heart attack or acute myocardial infarction (IMA) is a state of heart muscle necrosis due to an imbalance between oxygen demand and supply that occurs suddenly. IMA or heart attack is the most common cause of death in developed countries. Community service activities are carried out to increase knowledge of the elderly about Acute Myocardial Infarction or heart attacks which are expected to directly improve the health and quality of life of the elderly in Wonokromo Village. The time of the activity is carried out in a period of 1 week. The method used is to use the lecture method then proceed with an examination of blood pressure in the elderly. The level of knowledge of respondents can be known by doing a pre-test in the form of a questionnaire that will be filled by respondents to determine the level of knowledge of respondents regarding heart attacks. Pretest is done before counseling is given. Meanwhile, to know the increase in respondents' knowledge about the material can be known by comparing it with the results of the post test that has been filled out by the respondent after counseling. The outputs from the community service activities are reports that have been published in journals and increased respondents' understanding.